2009
DOI: 10.1177/030089160909500631
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Dependent Prolonged and Persistent Complete Remission Four Years from First Recurrence of Secondary Breast Angiosarcoma

Abstract: Among angiosarcomas, radiation-induced breast sarcomas (RIBS) represent a well-known entity generally characterized by a poor outcome, especially in patients with advanced disease. Despite the unfavorable prognosis, some chemotherapeutic agents have been used to treat these malignancies, occasionally with success. Treatments with demonstrated activity against sarcomas include ifosfamide-based regimens and, more recently, taxane derivatives. We report a case of a patient having a secondary breast angiosarcoma r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The former only administered docetaxel during the period of radiotherapy; the latter continued chemotherapy until the patient experienced PD . Similarly, Gambini et al . reported a patient with angiosarcoma who had maintenance chemotherapy for 4 years and was alive without disease, and Rhomberg et al .…”
Section: Discussionmentioning
confidence: 96%
“…The former only administered docetaxel during the period of radiotherapy; the latter continued chemotherapy until the patient experienced PD . Similarly, Gambini et al . reported a patient with angiosarcoma who had maintenance chemotherapy for 4 years and was alive without disease, and Rhomberg et al .…”
Section: Discussionmentioning
confidence: 96%
“…[37] Other groups have described promising responses to paclitaxel or gemcitabine-taxane (including complete remissions) for resectable primary or recurrent RAAS breast disease. [40-43] These findings highlight the need for well-designed trials to inform the true utility of chemotherapy in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Chemotherapy and radiotherapy may have roles to play in cases of unsuccessful surgical clearance; their beneficial effects remain to be defined. [24, 25, 37, 39, 41, 43, 46, 47] Accordingly, well-designed multicenter clinical trials are now urgently needed to advance RAAS care.…”
Section: Discussionmentioning
confidence: 99%
“…A small single-center study ( n  = 14) that looked at hyperfractionated and accelerated radiotherapy (HART), with or without surgical resection, found a 64 % 5-year progression-free survival 9. Other studies reported a good response to (neo-) adjuvant treatment with paclitaxel in some patients 12 , 21 , 22. Interpretation of these results is hampered by the limited number of cases and the heterogeneity of the study populations.…”
Section: Discussionmentioning
confidence: 99%